2005
DOI: 10.1111/j.1365-2133.2005.06816.x
|View full text |Cite
|
Sign up to set email alerts
|

The tumour necrosis factor-alpha inhibitor adalimumab rapidly reverses the decrease in epidermal Langerhans cell density in psoriatic plaques

Abstract: These data shed light on a new immunopathological perspective highlighting a rapid loss of epidermal LCs in acute psoriatic lesions, with sustained decreased density of LCs in chronic plaques. Furthermore, an unexpected insight into the mechanism of action was uncovered for adalimumab, in which rapid restoration of epidermal LC density was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 43 publications
7
46
1
2
Order By: Relevance
“…Deguchi et al, showed that the number of CD1a-positive epidermal langerhans cells in psoriatic lesions was not significantly different from that of normal controls, while we found higher epidermal CD1a+ cells infiltrate in lesional and non lesional skin than in controls [16]. Other studies reported variable results [17,18]. Recent evidences suggest impaired migration of Langerhans cells in early onset psoriasis [19].…”
Section: Discussioncontrasting
confidence: 36%
“…Deguchi et al, showed that the number of CD1a-positive epidermal langerhans cells in psoriatic lesions was not significantly different from that of normal controls, while we found higher epidermal CD1a+ cells infiltrate in lesional and non lesional skin than in controls [16]. Other studies reported variable results [17,18]. Recent evidences suggest impaired migration of Langerhans cells in early onset psoriasis [19].…”
Section: Discussioncontrasting
confidence: 36%
“…The return to the normal organization of epidermis resulted in reappearance of LCs -common constituent of basal and suprabasal layers. Similar effect was observed in psoriatic lesional skin after adalimumab -TNF-α inhibitor [40] and cyclosporine A [41], however Prignano et al [42] reported a 70% decrease of LCs number in psoriatic plaques 4 months after biological therapies. Normalization of the distribution of LCs in psoriasis was reported after systemic aromatic retinoid i.e.…”
Section: Density Of Langerhans Cells In Chronic Plaque Psoriatic Lesimentioning
confidence: 61%
“…Moreover, though the frequency and morphology of epidermal LCs in uninvolved skin of psoriatics is normal, these cells present impaired migration in response to stimuli such as allergens [27]. Whether the alterations in LC density in psoriatic plaques and the impaired LC migration from uninvolved skin influence contact sensitivity and PT reactivity remains to be determined [26, 27]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous immunologic studies indicated that psoriatics have a decreased prevalence of sensitization to experimental allergens and prolonged time of sensitization, and a higher allergen concentration is required to elicit an allergic response [20, 24, 25]. In the psoriatic plaque, compared with uninvolved skin of patients with psoriasis, CD1a+ CD207+ Langerhans cells (LCs), a type of immature dendritic cell in the epidermis, are present at reduced density [26]. Moreover, though the frequency and morphology of epidermal LCs in uninvolved skin of psoriatics is normal, these cells present impaired migration in response to stimuli such as allergens [27].…”
Section: Discussionmentioning
confidence: 99%